Sustainability of the Pension System, Risks and Opportunities - Péter, Ákos; Németh, Erzsébet; Vargha, Bálint Tamás (Public Finance Quarterly, 2020)
All other things being equal by 2060 out of 10 of the working age population 6 pensioners will be accounted for. This does constitute a risk for the sustainability of pensions. Our study has analysed the most recent data on demographics, economy, employment, and its underlying factors, as well as the expected development of the figures of the pension fund. Our findings point to that the shrinking of the population of women of childbearing age will result in a constant decrease of birth rates even by a modest increase in fertility rates. Therefore, family policy measures - being indispensable - are of their own insufficient to mitigate the economic and pension risks. Due to its conjunctural nature economic growth can only temporarily mitigate the risks. On the other hand, the extension of the labour market activity of elderly people can set back the increase in pension costs with well predictable efficiency. Means to this end can include promoting activity at old ages, raising retirement ages, preserving physical and mental well-being and employability, as well as spreading the culture of self-reliance.